Increased Mortality Among Persons With Symptomatic Coronavirus Disease 2019 (COVID-19) During the Period of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) B.1.617.2 (Delta Variant) Predominance: Alaska, November 2020–October 2021 . (29th June 2022) - Mooring, Eric Q; Newell, Katherine; Castrodale, Louisa; Tompkins, Megan; Frank, Morgan; McLaughlin, Joseph
Abstract: We compared the mortality risk in Alaska among persons with symptomatic coronavirus disease 2019 (COVID-19) during the period the Delta variant was predominant to the risk among those with symptomatic COVID-19 before Delta predominance. The Delta period was associated with 2.43-fold higher odds of death. Unvaccinated persons were 4.49 times more likely to die than fully vaccinated persons.